Steady transonic dense gas flow past two‐dimensional compression/expansion ramps. Issue 1 (15th March 2018) - Kluwick, Alfred; Cox, Ted
Abstract: The dynamic behaviour of compressible fluids depends crucially on the curvature of isentropes in the pressure/specific volume diagram. Most conveniently this curvature is expressed in form of a non‐dimensional quantity Γ now commonly referred to as the fundamental derivative of gasdynamics, Thompson [5]. Bethe‐Zel'dovich‐Thompson (BZT) fluids have the distinguishing property that they exhibit embedded regions in the general neighbourhood of the thermodynamic critical point where Γ is negative in contrast to classical gases of low molecular complexity including perfect gases where Γ is strictly positive. The behaviour of steady transonic flows of such fluids is essentially governed by two non‐dimensional parameters: (Γ) and its derivative with respect to the density at constant entropy (Λ), Cramer and Fry [2], Kluwick [4]. The resulting response to external forcing is surprisingly rich in nonclassical phenomena such as rarefaction shocks, sonic shocks, split shocks, etc. and is studied in detail for the canonical problem of two‐dimensional flow past compression/expansion ramps. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)